2008
DOI: 10.1002/app.28443
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the interaction of CO2 with poly (L‐lactide), poly(DL‐lactide) and poly(ε‐caprolactone) using FTIR spectroscopy

Abstract: Fourier transform infrared (FTIR) spectroscopy was used to reveal intermolecular interactions between carbon dioxide (CO 2 ) and the carbonyl groups of poly(L-lactide) (PLLA), poly(D,L-lactide) (PDLLA), and poly(e-caprolactone) (PCL). After exposing polymer films to high pressure CO 2 , the wave number of the absorption maxima of the polymer carbonyl groups shifted to higher values. Also, due to the interaction between CO 2 and the carbonyl groups of the polymers, a new broad peak in the bending mode region of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…As the peaks observed at 648 and 676 cm À1 can be assigned to CO 2 bending modes, which become Raman active by the interaction process, their presence in the Raman spectra of CO 2 -saturated PCL suggests that carbon dioxide is present in PCL in at least two 'populations', as also reported by Nawalade et al [10]: one 'polymer-associated', i.e. interacting with the PCL, and the other 'nonassociated'.…”
Section: Analysis Of Pcl/co 2 Spectramentioning
confidence: 71%
See 1 more Smart Citation
“…As the peaks observed at 648 and 676 cm À1 can be assigned to CO 2 bending modes, which become Raman active by the interaction process, their presence in the Raman spectra of CO 2 -saturated PCL suggests that carbon dioxide is present in PCL in at least two 'populations', as also reported by Nawalade et al [10]: one 'polymer-associated', i.e. interacting with the PCL, and the other 'nonassociated'.…”
Section: Analysis Of Pcl/co 2 Spectramentioning
confidence: 71%
“…For this reason, spectroscopic techniques, such as Attenuated Total Reflectance (ATR), Fourier Transformed Infrared (FTIR) and Raman spectroscopy, are being widely used for the investigation of sorption behaviour of CO 2 (and of other low molecular weight penetrants) in polymers, as they provide useful information on both local gas concentration and on possible specific polymer/gas interactions. Actually, investigations based on the use of ATR and FTIR have revealed that CO 2 interacts with most polymers [9,10] as specific spectroscopic features of the solution (such as the observation of the splitting of the peak assigned to CO 2 bending mode) have been demonstrated to be the evidence of the interaction between the gas molecules and the polymer [8,9].…”
Section: Introductionmentioning
confidence: 98%
“…In addition, the CO 2 sorption in the starch matrix is relatively low compared with other semicrystalline polymers at the similar temperature and pressure range (Table 4). The differences in the CO 2 sorption of NPS compared with other materials may be due to differences in the physical properties (such as glass transition temperature ( T g ) and melting temperature ( T m )), morphological characteristics (such as the degree of crystallinity and swelling of the polymers) and also the occurrence of intermolecular interaction between CO 2 and the functional groups present in the polymers [18, 20, 26, 27, 32–37].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it can be concluded that the solubility of CO 2 in SA is higher than in NPS at all pressure values. The difference in the CO 2 solubility between NPS and SA may be related to a reduction in the crystallinity after the acetylation reaction ( vide supra ) [38, 39] and favorable intermolecular interaction between CO 2 and SA due to the presence of the carbonyl group (CO) in the SA matrix [32, 40, 41] (see later).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation